2008 5th IEEE International Symposium on Biomedical Imaging: From Nano to Macro 2008
DOI: 10.1109/isbi.2008.4541209
|View full text |Cite
|
Sign up to set email alerts
|

Intersection based registration of slice stacks to form 3D images of the human fetal brain

Abstract: Clinical fetal MR imaging of the brain commonly makes use of fast 2D acquisitions of multiple sets of approximately orthogonal 2D slices. We and others have previously proposed an iterative slice-to-volume registration process to recover a geometrically consistent 3D image. However, these approaches depend on a 3D volume reconstruction step during the slice alignment. This is both computationally expensive and makes the convergence of the registration process poorly defined. In this paper our key contribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…Recent studies on human brain development of fetuses using 2D MR slices can be found in [13]–[15]. The first automated tissue segmentation of developing tissues from motion corrected un-sedated fetal brain anatomy was recently described in utero [16] following the development of 3D reconstruction techniques [17]–[19]. …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on human brain development of fetuses using 2D MR slices can be found in [13]–[15]. The first automated tissue segmentation of developing tissues from motion corrected un-sedated fetal brain anatomy was recently described in utero [16] following the development of 3D reconstruction techniques [17]–[19]. …”
Section: Introductionmentioning
confidence: 99%
“…Here we employ Slice Intersection Motion Correction [15,16] to estimate individual slice motion. This approach, in effect, extends 2D image mosaicing to the extreme case of considering overlap at the intersection of any pairs of slices that have been acquired in approximately orthogonal orientations.…”
Section: Methodsmentioning
confidence: 99%
“…The MR sequence parameters (TR = 4000–8000ms, TE = 91ms) were originally designed for clinical scans and cannot be adjusted for image analysis purposes. After acquisition, image stacks are registered using an intersection-based technique [7] to account for spontaneous fetal movement during scanning and reconstructed into 3D volumes with isotropic resolution 0.469mm × 0.469mm × 0.469mm. Reconstructed volumes are manually segmented into regions of cortical grey matter (GM), white matter (WM), the germinal matrix (GMAT) and ventricles (VENT).…”
Section: Methodsmentioning
confidence: 99%